Effects of typhoons on an arthropod community centered upon a leaf gall midge, Pseudasphondylia neolitseae (Diptera: Cecidomyiidae) and its host plant, Neolitsea sericea (Lauraceae) through leaf fall and late‐season shoot production. Issue 1 (17th December 2019) - Yukawa, Junichi; Fujimoto, Kenji; Ganaha‐Kikumura, Tomoko; Kim, Wanggyu
Abstract: We evaluated effects of strong typhoons on populations of a gall midge Pseudasphondylia neolitseae (Diptera: Cecidomyiidae) and its associated arthropods through leaf fall of the host plant, Neolitsea sericea (Lauraceae). The very strong typhoon No. 13 in 1985 ("8513‐Pat") caused heavy leaf fall particularly on forest edge trees, resulted in the larval death of gall midge and its endoparasitoid Gastrancistrus sp. (Hymenoptera: Pteromalidae). The typhoons were not directly responsible for the larval death of an ectoparasitoid Bracon tamabae (Hymenoptera: Braconidae) and a successor Lasioptera yadokariae (Diptera: Cecidomyiidae) that utilizes vacant galls after the departure of inhabitants. However, reduction in the number of galls possibly made their searching behavior for oviposition sites inefficient because their abundance relies on the gall density. The heavy leaf fall promoted lammas shoot production, which caused the reduction of number and length of the following spring shoots. The shortage of spring shoots must be influential to the gall midge females in searching oviposition sites, and the short spring shoots were not useful for oviposition and larval boring by Oberea hebescens (Coleoptera: Cerambycidae). We compared strength of the effects between the typhoons that attacked Kagoshima in 1985 and 1993, and Okinawa in 2015 and 2018, and concluded that typhoons with the maximum instantaneous wind velocity exceeding 50 m/s caused heavy leaf fall and lammas shoot production on N . sericea trees growing at forest edge but not on those inside forest. Abstract : This is the first report dealing with direct and indirect effects of powerful typhoons on an arthropod community associated with a particular plant species. This kind of abiotic data is essential to evaluate community dynamics in addition to biotic factors.